Evaluation of Accuracy of an Indigenous Cost-Effective and User-Friendly Alarm System for Monitoring of Intravenous Infusion- IV ALERT. Issue 3 (3rd April 2023) - Puri, Goverdhan Dutt; Samra, Tanvir; Jindal, Arvind; Singla, Harshit; Konar, Sushant
Abstract : " IV ALERT " is a portable and light-weight device for monitoring the volume of fluid delivered from a gravity-fed infusion bottle and activating an alarm at 80%, 90% and 100% of the preset target volume. A load cell with a high accuracy strain gauge is used to activate a microcontroller and an internal timer. We hypothesized that the accuracy of the device to sound an alarm will be unaffected by the viscosity of the fluid suspended. The experimental set-up was established after ethical approval. Normal saline, Ringer's Lactate, Dextrose 5% and Dextrose Normal Saline were suspended with different settings of target volume from the device. The drained volume of fluid was collected in the measuring cylinder and the experiment terminated on activation of the alarm. Calculation of the percentage error difference between the measured volume and theoretical value (preset target volume), divided by the theoretical value and multiplied by 100 was used to assess the accuracy of the device to sound the alarms. Total of 1818 observations were made and the percentage error was 0.017 ± 0.016 (mean ± SD) which was comparable at 80%, 90% or 100% of set target volumes for all the four types of fluids. Using the same principle in the reverse order, it is being tested as a urinometer where increase in weight of the urobag suspended from it due to the collection of urine is displayed as volume. IV Alert has also been made Wi-Fi-enabled for remote monitoring from the nursing station.